Weight loss in combat sports: physiological, psychological and performance effects - Franchini, E.; Brito, C. J.; Artioli, G. G. (Journal of the International Society of Sports Nutrition, 2012)
The present article briefly reviews the weight loss processes in combat sports. We aimed to discuss the most relevant aspects of rapid weight loss (RWL) in combat sports Methods This review was performed in the databases MedLine, Lilacs, PubMed and SciELO, and organized into sub-topics: (1) prevalence, magnitude and procedures, (2) psychological, physiological and performance effects, (3) possible strategies to avoid decreased performance (4) organizational strategies to avoid such practices Results There was a high prevalence (50%) of RWL, regardless the specific combat discipline. Methods used are harmful to performance and health, such as laxatives, diuretics, use of plastic or rubber suits, and sauna. RWL affects physical and cognitive capacities, and may increase the risk of death Conclusion Recommendations during different training phases, educational and organizational approaches are presented to deal with or to avoid RWL.